Preparing patient navigators and assessing the impact of patient navigation in promoting cervical cancer screening uptake, knowledge, awareness, intention, and health beliefs: a protocol for a randomized controlled trial - Mboineki, Joanes Faustine; Chen, Changying (Frontiers in Global Women's Health, 2024)
AimThere are limited studies in Tanzania concerning the modality of preparing patient navigators and the influence of patient navigation strategies on cervical cancer screening. This protocol describes the preparation of patient navigators and assesses the impact of a patient navigation strategy on promoting cervical cancer screening uptake, knowledge, awareness, intention, and health beliefs.DesignThis is a protocol for a community-based randomized controlled trial.MethodsThe method is categorized into two phases. (1) Preparing patient navigators, which will involve the training of five patient navigators guided by a validated training manual. The training will be conducted over three consecutive days, covering the basic concepts of cervical cancer screening and guiding navigators on how to implement a patient navigation strategy in the communities. (2) Delivering a patient navigation intervention to community women (COMW) which will involve health education, screening appointments, navigation services, and counseling. The study will recruit 202 COMW who will be randomized 1:1 by computer-based blocks to either the patient navigation intervention group or the control group.Public contributionThe study will prove that the trained patient navigators are easily accessible and offer timely and culturally acceptable services to promote cervical cancer screening uptake in communities.